Organic matter-based wave-absorbing composite material filled with two-dimensional ferrite film and preparation method of organic matter-based wave-absorbing composite material
By preparing a two-dimensional ferrite film on a single crystal substrate of SrTiO3 and preparing a multi-layer structure in combination with hot pressing, the problems of ferrite powder prone to agglomeration and electromagnetic wave bypassing are solved, and the performance of wave absorbing materials is significantly improved.
Patent Information
- Application Number
- CN202411857718.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-02-25
AI Technical Summary
In the existing ferrite/organic composite materials, ferrite powders are prone to agglomeration and electromagnetic waves are easily bypassed, resulting in a degradation of wave absorption performance.
A two-dimensional ferrite film was prepared on a single crystal substrate of SrTiO3 using pulsed laser deposition technology, and the film was peeled off by the water-soluble method, and a multi-layer wave-absorbing composite material composed of "organic film/ferrit film/organic film" was prepared in combination with the hot pressing method.
It effectively avoids the agglomeration of ferrite powder and electromagnetic wave bypassing, and improves the electromagnetic wave absorption performance and absorption efficiency of composite materials.
Smart Images

Figure CN119521642A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of, but is not limited to, electromagnetic absorbing material technology, and in particular to an organic-based absorbing composite material filled with a two-dimensional ferrite film and a preparation method thereof. Background Art
[0002] As a material that can effectively absorb electromagnetic waves, absorbing materials have the property of converting the energy of electromagnetic waves into heat energy or other forms of energy, thereby reducing or eliminating the interference of electromagnetic waves on the surrounding environment. Therefore, absorbing materials have broad application prospects in the fields of electromagnetic wave isolation, wireless communication equipment, etc.
[0003] Ferrite / organic composite materials are a common absorbing material that has attracted much attention due to their excellent absorbing properties of ferrite and the impedance matching characteristics of organic matter. At present, the traditional preparation method of ferrite / organic composite materials is to mix ferrite powders of different particle sizes and shapes with organic matter by physical stirring. Although this preparation method is simple to operate, the preparation process and the product have the following disadvantages: the ferrite powder particles in the prepared ferrite / organic composite material are easy to agglomerate, and electromagnetic waves can easily bypass the ferrite powder particles, which leads to the problem of decreased absorbing performance of the composite material. Summary of the invention
[0004] Purpose of the present invention: In order to solve the above-mentioned technical problems, the embodiments of the present invention provide an organic-based absorbing composite material filled with a two-dimensional ferrite film and a preparation method thereof, so as to solve the problem that ferrite powder particles in the existing ferrite / organic composite materials are easy to agglomerate, and electromagnetic waves are easy to bypass the ferrite powder particles, thereby causing a decrease in the absorbing performance of the composite material.
[0005] Technical solution of the present invention: In a first aspect, an embodiment of the present invention provides a method for preparing an organic-based microwave absorbing composite material filled with a two-dimensional ferrite film, characterized in that it comprises:
[0006] Step 1, on a single crystal substrate of SrTiO3, using a ferrite target and a Sr3Al2O6 target, a pulsed laser deposition technique is used to prepare a "ferrite / Sr3Al2O6 / SrTiO3" heterostructure;
[0007] Step 2, using a water-soluble method to peel off the two-dimensional ferrite film in the "ferrite / Sr3Al2O6 / SrTiO3" heterostructure, and prepare a "ferrite / PDMS" heterostructure;
[0008] Step 3, on a single crystal silicon substrate, a mixed solution for forming an organic film is spin-coated by a spin coating method to prepare an "organic film / Si" heterostructure;
[0009] Step 4, hot pressing the "ferrite / PDMS" heterostructure and the "organic film / Si" heterostructure by hot pressing to prepare an organic / ferrite / organic multilayer absorbing composite material filled with a two-dimensional ferrite film.
[0010] Optionally, in the method for preparing an organic-based microwave-absorbing composite material filled with a two-dimensional ferrite film as described above,
[0011] The step 1 comprises: using Ni 0.5 Zn 0.5 Fe2O4 target and Sr3Al2O6 target, and the "Ni" filled with two-dimensional ferrite film was prepared by pulsed laser deposition technology. 0.5 Zn 0.5 Fe2O4 / Sr3Al2O6 / SrTiO3” heterostructure;
[0012] The step 2 comprises: using a water-soluble method to dissolve the "Ni 0.5 Zn 0.5 Ni in the "Fe2O4 / Sr3Al2O6 / SrTiO3" heterostructure 0.5 Zn 0.5 The Fe2O4 film was peeled off and the "Ni 0.5 Zn 0.5 Fe2O4 / PDMS” heterostructure;
[0013] The step 3 comprises: on a single crystal silicon (Si) substrate, using a spin coating method to spin-coat a mixed solution for forming an organic film to prepare an "organic film / Si" heterostructure;
[0014] The step 4 comprises: 0.5 Zn 0.5 The "Fe2O4 / PDMS" heterostructure and the "organic film / Si" heterostructure are hot-pressed by hot pressing to prepare the organic-based microwave absorbing composite material "organic film / Ni" filled with a two-dimensional ferrite film. 0.5 Zn 0.5 Fe2O4 / organic film".
[0015] Optionally, in the method for preparing the organic-based microwave absorbing composite material filled with a two-dimensional ferrite film as described above, the step 1 comprises:
[0016] Step 1.1, growing a Sr3Al2O6 thin film on the SrTiO3 single crystal substrate to prepare a "Sr3Al2O6 / SrTiO3" heterostructure;
[0017] Step 1.2, growing Ni on the “Sr3Al2O6 / SrTiO3” heterostructure 0.5 Zn 0.5 Fe2O4 thin film, prepared "Ni 0.5 Zn 0.5 Fe2O4 / Sr3Al2O6 / SrTiO3" heterostructure; wherein the Ni 0.5 Zn 0.5 The Fe2O4 film is grown on one side of the Sr3Al2O6 film of the "Sr3Al2O6 / SrTiO3" heterostructure.
[0018] Optionally, in the method for preparing the organic-based microwave-absorbing composite material filled with a two-dimensional ferrite film as described above, the step 2 comprises:
[0019] Step 2.1, in the “Ni 0.5 Zn 0.5 The "PDMS / Ni" heterostructure was prepared by electrostatically adsorbing polydimethylsiloxane PDMS film on the Fe2O4 / Sr3Al2O6 / SrTiO3 0.5 Zn 0.5 Fe2O4 / Sr3Al2O6 / SrTiO3" heterogeneous structure; the PDMS film is adsorbed on the "Ni 0.5 Zn 0.5 "Fe2O4 / Sr3Al2O6 / SrTiO3" heterostructured Ni 0.5 Zn 0.5 Fe2O4 membrane side;
[0020] Step 2.2, the "PDMS / Ni 0.5 Zn 0.5 The "Fe2O4 / Sr3Al2O6 / SrTiO3" heterostructure was placed in deionized water to dissolve the Sr3Al2O6 film and prepare the "Ni 0.5 Zn 0.5 Fe2O4 / PDMS” heterostructure.
[0021] Optionally, in the method for preparing the organic-based microwave-absorbing composite material filled with a two-dimensional ferrite film as described above, step 3 comprises:
[0022] Step 3.1, dissolving PI powder in N,N-dimethylformamide DMF solvent to prepare a PI / DMF mixed solution for spin coating to form a PI film;
[0023] Step 3.2, spin coating the PI / DMF mixed solution on a Si substrate and drying it to prepare the "PI / Si" heterostructure.
[0024] Optionally, in the method for preparing the organic-based microwave-absorbing composite material filled with a two-dimensional ferrite film as described above, step 4 comprises:
[0025] Step 4.1, the "Ni 0.5 Zn 0.5 The "Fe2O4 / PDMS" heterostructure was hot pressed onto the PI layer surface of the PI / Si heterostructure prepared in step 1.3 to prepare the "PDMS / Ni 0.5 Zn 0.5 Fe2O4 / PI / Si" heterostructure; wherein the "Ni 0.5 Zn 0.5 The NiFe2O4 / PDMS" heterostructure 0.5 Zn 0.5 The Fe2O4 layer is in direct contact with the PI layer of the "PI / Si" heterostructure, the hot pressing temperature is 250°C, and the hot pressing time is 30 minutes;
[0026] Step 4.2, using physical means to 0.5 Zn 0.5 The PDMS layer in the "Fe2O4 / PI / Si" heterostructure is peeled off to prepare the "Ni 0.5 Zn 0.5 Fe2O4 / PI / Si” heterostructure;
[0027] Step 4.3, using another PI / Si heterostructure, physically peeling the PI layer from the Si substrate to obtain a PI film;
[0028] Step 4.4, hot pressing the PI film onto the "Ni 0.5 Zn 0.5 Ni in the "Fe2O4 / PI / Si" heterostructure 0.5 Zn 0.5 The surface of the Fe2O4 layer is prepared to obtain "PI / Ni 0.5 Zn 0.5 Fe2O4 / PI / Si” heterostructure;
[0029] Step 4.5, the "PI / Ni 0.5 Zn 0.5 The "Fe2O4 / PI / Si" heterostructure was vacuum dried and kept warm, and then placed in deionized water at 0°C. The "PI / Ni 0.5 Zn 0.5 The Si layer in the "Fe2O4 / PI / Si" heterostructure is peeled off to prepare the organic-based microwave absorbing composite material PI / Ni filled with a two-dimensional ferrite film.0.5 Zn 0.5 Fe2O4 / PI.
[0030] Optionally, in the method for preparing an organic-based microwave-absorbing composite material filled with a two-dimensional ferrite film as described above, the organic film is a polyimide PI film; or a polyethyleneimine PEI film.
[0031] Optionally, in the method for preparing an organic-based microwave-absorbing composite material filled with a two-dimensional ferrite film as described above,
[0032] The step 1 comprises: using Mn 0.5 Zn 0.5 Fe2O4 target and Sr3Al2O6 target, and pulsed laser deposition technology was used to prepare the "Mn" filled with two-dimensional ferrite film 0.5 Zn 0.5 Fe2O4 / Sr3Al2O6 / SrTiO3” heterostructure;
[0033] The step 2 comprises: using a water-soluble method to dissolve the "Mn 0.5 Zn 0.5 Mn in the "Fe2O4 / Sr3Al2O6 / SrTiO3" heterostructure 0.5 Zn 0.5 The Fe2O4 film was peeled off and the "Mn 0.5 Zn 0.5 Fe2O4 / PDMS” heterostructure;
[0034] The step 3 comprises: on a single crystal silicon (Si) substrate, using a spin coating method to spin-coat a mixed solution for forming an organic film to prepare an "organic film / Si" heterostructure;
[0035] The step 4 comprises: 0.5 Zn 0.5 The "Fe2O4 / PDMS" heterostructure and the "organic film / Si" heterostructure are hot pressed to prepare the organic-based microwave absorbing composite material "organic film / Mn" filled with a two-dimensional ferrite film. 0.5 Zn 0.5 Fe2O4 / organic film".
[0036] Optionally, in the method for preparing an organic-based microwave-absorbing composite material filled with a two-dimensional ferrite film as described above, the organic film is a polyethyleneimine PEI film; or a PI film.
[0037] In a second aspect, an embodiment of the present invention further provides an organic-based absorbing composite material filled with a two-dimensional ferrite thin film, wherein the organic-based absorbing composite material filled with a two-dimensional ferrite thin film is prepared by a preparation method as described in any one of the above items, comprising: a ferrite thin film with a thickness of 50 to 200 nm, and an organic film with a thickness of 3 to 7 μm; the organic-based absorbing composite material is a multilayer structure consisting of "organic film / ferrite film / organic film".
[0038] Optionally, in the organic-based wave-absorbing composite material filled with a two-dimensional ferrite film as described above, the ferrite film comprises one of the following films: Ni 0.5 Zn 0.5 Fe2O4 film, Mn 0.5 Zn 0.5 Fe2O4 film.
[0039] Optionally, in the organic-based microwave-absorbing composite material filled with a two-dimensional ferrite film as described above, the organic film comprises one of the following thick films: a polyimide PI film and a polyethyleneimine PEI film.
[0040] Optionally, in the organic-based wave-absorbing composite material filled with a two-dimensional ferrite film as described above, the multilayer structure of "organic film / ferrite film / organic film" comprises: "PI / Ni 0.5 Zn 0.5 Fe2O4 / PI" multilayer structure, or "PI / Mn 0.5 Zn 0.5 Fe2O4 / PI" multilayer structure, or "PEI / Ni 0.5 Zn 0.5 Fe2O4 / PEI" multilayer structure, or "PEI / Mn 0.5 Zn 0.5 Fe2O4 / PEI” multilayer structure.
[0041] Beneficial effects of the invention: The embodiment of the invention provides an organic-based microwave absorbing composite material filled with a two-dimensional ferrite film and a preparation method thereof, which has the following beneficial effects:
[0042] On the one hand, an organic-based absorbing composite material includes: a ferrite film with a thickness of 50 to 200 nm, and an organic film with a thickness of 3 to 7 μm; the organic-based absorbing composite material is a multilayer structure composed of "organic film / ferrite film / organic film". In the organic-based absorbing composite material filled with a two-dimensional ferrite film, the ferrite exists in the form of a film to avoid the agglomeration of ferrite powder particles and the occurrence of electromagnetic waves bypassing ferrite particles. The material has good electromagnetic wave absorption performance and high electromagnetic wave absorption efficiency. The above-mentioned film thickness range is conducive to improving the electromagnetic wave absorption performance of the organic-based absorbing composite material.
[0043] On the other hand, the preparation method of the organic-based absorbing composite material filled with two-dimensional ferrite film includes: on a SrTiO3 single crystal substrate with a crystal orientation of (100), using a ferrite target and a Sr3Al2O6 target, using a pulsed laser deposition technology to prepare a "ferrite / Sr3Al2O6 / SrTiO3" heterostructure filled with a two-dimensional ferrite film; using a water-soluble method to peel off the ferrite film in the above heterostructure to prepare a "ferrite / PDMS" heterostructure; on a single crystal silicon (Si) substrate, using a spin coating method to spin coat a mixed solution of an organic film to prepare an "organic film / Si" heterostructure; hot pressing the "ferrite / PDMS" heterostructure and the "organic film / Si" heterostructure by a hot pressing method to prepare an organic-based absorbing composite material filled with a two-dimensional ferrite film. The above-mentioned preparation process is simple, and the agglomeration of ferrite particles is avoided during the preparation process, thereby ensuring the contact area between the powder particles and the electromagnetic waves and thus improving the wave absorbing performance of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] The accompanying drawings are used to provide a further understanding of the technical solution of the present invention and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the technical solution of the present invention and do not constitute a limitation on the technical solution of the present invention.
[0045] Figure 1 The "PI / Mn" provided in the embodiment of the present invention 0.5 Zn 0.5 Schematic diagram of the structure of the organic-based microwave absorbing composite material with a multilayer structure of "Fe2O4 / PI";
[0046] Figure 2 The "PI / Ni" provided in the embodiment of the present invention 0.5 Zn 0.5 Scanning electron microscope image of organic-based microwave absorbing composite material with multilayer structure of “Fe2O4 / PI”;
[0047] Figure 3 The "PEI / Mn" provided in the embodiment of the present invention 0.5 Zn0.5 Scanning electron microscope image of organic-based absorbent composite material with “Fe2O4 / PEI” multilayer structure. DETAILED DESCRIPTION
[0048] In order to make the purpose, technical solution and advantages of the present invention more clear, the embodiments of the present invention will be described in detail with reference to the accompanying drawings. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other arbitrarily without conflict.
[0049] The above background technology has already explained the role of absorbing materials and their broad application prospects. As a common absorbing material, ferrite / organic composite materials have the following disadvantages in traditional preparation methods and products:
[0050] On the one hand, ferrite powder particles are easily agglomerated in the composite material, which reduces the contact area between the powder particles and electromagnetic waves, resulting in a decrease in the composite material's absorbing performance; on the other hand, electromagnetic waves can easily bypass the ferrite powder particles and penetrate the composite material, which also results in a decrease in the composite material's absorbing performance.
[0051] Based on the above analysis, it can be seen that obtaining an absorbing composite material with no agglomeration of ferrite powder particles and preventing electromagnetic waves from bypassing ferrite particles has become a technical problem that needs to be solved urgently. In response to the above problems and the performance requirements of absorbing composite materials, the present invention provides an organic-based absorbing composite material filled with a two-dimensional ferrite film and a preparation method thereof.
[0052] Among the absorbing materials, ferrite / organic composite materials are a common absorbing material. Since the composite material has a simple preparation method and the material itself can combine the magnetic loss characteristics of ferrite with the impedance matching characteristics of organic matter, thereby broadening the material's own absorbing frequency band and improving the absorbing efficiency, the composite material has a wide range of applications in the fields of electromagnetic wave isolation and wireless communication equipment. However, in the existing ferrite / organic composite materials, ferrite powder often exists in the form of particles. On the one hand, granular ferrite powder is easy to agglomerate in the composite material, which leads to a decrease in the contact area between the powder particles and the electromagnetic wave; on the other hand, granular ferrite powder is easy to be bypassed by electromagnetic waves and then penetrate the composite material; both of the above situations will have an adverse effect on the absorbing performance of the composite material.
[0053] Based on the above problems existing in the existing ferrite / organic composite materials, an embodiment of the present invention provides an organic-based microwave absorbing composite material filled with a two-dimensional ferrite film and a preparation method thereof.
[0054] The present invention provides the following specific embodiments which can be combined with each other. The same or similar concepts or processes may not be described in detail in some embodiments.
[0055] Embodiment 1
[0056] The embodiment of the present invention provides an organic-based wave-absorbing composite material filled with a two-dimensional ferrite film, the material comprising: a ferrite film with a thickness of 50 to 200 nm, and an organic film with a thickness of 3 to 7 μm; the composite material is a multilayer structure of "organic film / ferrite film / organic film". The organic films in the multilayer structure can be of the same type or of different types. For example, "PEI / Mn 0.5 Zn 0.5 Fe2O4 / PEI", "PI / Mn 0.5 Zn 0.5 Fe2O4 / PEI”, etc. For ease of understanding, the embodiments of the present invention are all illustrated by taking the organic membrane as the same type. Figure 1 Instructions in the Appendix Figure 1 The "PI / Mn" provided in the embodiment of the present invention 0.5 Zn 0.5 Schematic diagram of the structure of organic-based microwave-absorbing composite materials with "Fe2O4 / PI" multilayer structure. Figure 1 As shown in the figure, the composite material presents a multi-layer sandwich structure as a whole. The upper and lower layers of the sandwich structure are both organic PI films, and the ferrite film in the middle layer is Mn 0.5 Zn 0.5 Fe2O4 film.
[0057] Optionally, the ferrite film of the organic-based wave-absorbing composite material includes any one of the following films: Ni 0.5 Zn 0.5 Fe2O4 film, Mn 0.5 Zn 0.5 Fe2O4 film, Fe3O4 film, BiFeO3 film. It should be understood that ferrite, as a magnetic loss absorbing material, can effectively convert electromagnetic waves into heat energy; in the embodiment of the present invention, the ferrite is prepared in the form of a film and filled into an organic-based absorbing composite material, which can avoid the agglomeration of particles when the ferrite exists in the form of powder particles and the phenomenon of electromagnetic waves bypassing the ferrite particles. The existence of this ferrite film structure effectively improves the electromagnetic wave absorption performance of the composite material, and its electromagnetic wave absorption efficiency is high.
[0058] Optionally, the above-mentioned organic film includes any one of the following thick films: polyimide (PI) film, polyethyleneimine (PEI) film, polymethyl methacrylate (PMMA) film. It should be understood that the above-mentioned organic film is a wave-transmitting material that can transmit electromagnetic waves to the surface of the ferrite film; different types of wave-transmitting materials have different electromagnetic wave transmission properties. The above-mentioned polyimide (PI) film, polyethyleneimine (PEI) film, and polymethyl methacrylate (PMMA) film selected in the embodiments of the present invention have excellent wave transmission properties. Of course, as the outermost structure of the multi-layer composite material, the two outer organic films can have the same thickness or a difference in thickness. For example, "PEI / Mn 0.5 Zn 0.5 In the organic-based microwave absorbing composite material with "Fe2O4 / PEI" multilayer structure, Mn 0.5 Zn 0.5 The thickness of the Fe2O4 film layer is 50 nm, and the thickness of the two outer PEI films are 4 μm and 5 μm respectively. The embodiment of the present invention is only an illustration and is not actually limiting.
[0059] In the embodiment of the present invention, as a feasible implementation method, the Ni 0.5 Zn 0.5 The Fe2O4 film and the PI film with a thickness of about 4 to 5 μm together form a multilayer structure of an organic-based microwave absorbing composite material filled with a two-dimensional ferrite film, namely "PI / Ni 0.5 Zn 0.5 Fe2O4 / PI" multilayer structure organic-based absorbing composite material. It should be understood that the range of the above film thickness is limited to Ni with a preferred thickness of about 80 to 120 nm. 0.5 Zn 0.5 The Fe2O4 film and the PI film with a thickness of about 4 to 5 μm are beneficial to the improvement of the electromagnetic wave absorbing performance of the organic-based absorbing composite material. 0.5 Zn 0.5 The thickness of the Fe2O4 film can also be selected as 200nm, and the thickness of the PI film can also be selected as 3μm. For specific examples, please refer to the attached Figure 2 ; Attachment Figure 2 The "PI / Ni" provided in the embodiment of the present invention 0.5 Zn 0.5 Schematic diagram of the scanning electron microscope image of the organic-based absorbent composite material with a multilayer structure of "Fe2O4 / PI".
[0060] In the embodiment of the present invention, as another feasible implementation, the Mn layer preferably has a thickness of about 80 to 120 nm. 0.5 Zn 0.5The Fe2O4 film and the PI film with a thickness of about 4 to 5 μm together form a multi-layer structure of an organic-based microwave absorbing composite material filled with a two-dimensional ferrite film, namely "PI / Mn 0.5 Zn 0.5 Fe2O4 / PI” multilayer structure organic-based microwave absorbing composite material.
[0061] In the embodiment of the present invention, as another feasible implementation, the Ni 0.5 Zn 0.5 The Fe2O4 film and the PEI film with a thickness of about 4 to 5 μm together form a multilayer structure of an organic-based microwave absorbing composite material filled with a two-dimensional ferrite film, namely "PEI / Ni 0.5 Zn 0.5 Fe2O4 / PEI" multilayer structure organic-based microwave absorbing composite material.
[0062] In the embodiment of the present invention, as another feasible implementation, the Mn layer preferably has a thickness of about 80 to 120 nm. 0.5 Zn 0.5 The Fe2O4 film and the PEI film with a thickness of about 4 to 5 μm together form a multi-layer structure of an organic-based microwave absorbing composite material filled with a two-dimensional ferrite film, namely "PEI / Mn 0.5 Zn 0.5 Fe2O4 / PEI" multilayer structure organic-based microwave absorbing composite material. It should be understood that the range of the above film thickness is limited to Mn with a preferred thickness of about 80 to 120 nm. 0.5 Zn 0.5 Fe2O4 film and PEI film with a thickness of about 4 to 5 μm are also conducive to improving the electromagnetic wave absorbing performance of organic-based absorbing composite materials. 0.5 Zn 0.5 The thickness of the Fe2O4 film can also be selected as 200nm, and the thickness of the PEI film can also be selected as 4μm. For specific examples, please refer to the attached Figure 3 ; Attachment Figure 3 The "PEI / Mn" provided in the embodiment of the present invention 0.5 Zn 0.5 Schematic diagram of the scanning electron microscope image of the organic-based absorbent composite material with a multilayer structure of "Fe2O4 / PEI".
[0063] Through the above embodiments, in the organic-based absorbing composite material filled with two-dimensional ferrite thin film, the ferrite in the form of a thin film in the composite material can avoid the agglomeration of ferrite powder particles and the occurrence of electromagnetic waves bypassing ferrite particles. The composite material has good electromagnetic wave absorption performance and high electromagnetic wave absorption efficiency. Furthermore, by adjusting the film thickness of the ferrite thin film and the organic film, it can be further beneficial to improve the electromagnetic wave absorption performance of the organic-based absorbing composite material.
[0064] Embodiment 2
[0065] The present invention provides a "PI / Ni" filled with a two-dimensional ferrite film. 0.5 Zn 0.5 A method for preparing a Fe2O4 / PI" organic-based wave-absorbing composite material, the method comprising the following steps:
[0066] Step 201: On a SrTiO3 single crystal substrate with a crystal orientation of (100), Ni 0.5 Zn 0.5 Fe2O4 target and Sr3Al2O6 target, and the "Ni" filled with two-dimensional ferrite film was prepared by pulsed laser deposition technology. 0.5 Zn 0.5 Fe2O4 / Sr3Al2O6 / SrTiO3" heterogeneous structure, the specific process is as follows:
[0067] Step 201-1, growing a Sr3Al2O6 thin film on a SrTiO3 single crystal substrate to prepare a "Sr3Al2O6 / SrTiO3" heterostructure;
[0068] Step 201-2: Growth of Ni in the "Sr3Al2O6 / SrTiO3" heterostructure 0.5 Zn 0.5 Fe2O4 thin film, prepared "Ni 0.5 Zn 0.5 Fe2O4 / Sr3Al2O6 / SrTiO3" heterostructure; among them, Ni 0.5 Zn 0.5 The Fe2O4 film is grown on the Sr3Al2O6 film side of the "Sr3Al2O6 / SrTiO3" heterostructure.
[0069] Specifically, a 50 nm thick Sr3Al2O6 film and a 50 nm thick Ni 0.5 Zn 0.5When growing Sr3Al2O6 thin film, the temperature of SrTiO3 single crystal substrate is 800℃, the distance between Sr3Al2O6 target and SrTiO3 single crystal substrate is 6cm, and the laser energy is 2J / cm 2 , laser frequency is 3Hz, oxygen pressure is 15Pa, growth time is 10min, and the "Sr3Al2O6 / SrTiO3" heterostructure is prepared. When Ni is grown on the "Sr3Al2O6 / SrTiO3" heterostructure 0.5 Zn 0.5 When Fe2O4 film is formed, the temperature of SrTiO3 single crystal substrate is 700℃, Ni 0.5 Zn 0.5 The distance between the Fe2O4 target and the SrTiO3 single crystal substrate is 6 cm, and the laser energy is 2 J / cm 2 , laser frequency is 3Hz, oxygen pressure is 5Pa, and growth time is 10min. Through the above process, "Ni 0.5 Zn 0.5 Fe2O4 / Sr3Al2O6 / SrTiO3” heterostructure.
[0070] Step 202: Using a water-soluble method, 0.5 Zn 0.5 Ni in the "Fe2O4 / Sr3Al2O6 / SrTiO3" heterostructure 0.5 Zn 0.5 The Fe2O4 film was peeled off and the "Ni 0.5 Zn 0.5 Fe2O4 / PDMS" heterostructure, the detailed process description is as follows:
[0071] Using the water-soluble method, Ni 0.5 Zn 0.5 Fe2O4 thin film from "Ni 0.5 Zn 0.5 The specific process is as follows: First, a 50 μm thick polydimethylsiloxane (PDMS) film is attached to the “Ni” by electrostatic adsorption. 0.5 Zn 0.5 Fe2O4 / Sr3Al2O6 / SrTiO3" heterostructure to obtain "PDMS / Ni 0.5 Zn 0.5 Fe2O4 / Sr3Al2O6 / SrTiO3" heterostructure; in which the PDMS membrane is adsorbed on "Ni 0.5 Zn 0.5 "Fe2O4 / Sr3Al2O6 / SrTiO3" heterostructured Ni 0.5 Zn0.5 Fe2O4 film side; then, the "PDMS / Ni 0.5 Zn 0.5 The "Fe2O4 / Sr3Al2O6 / SrTiO3" heterostructure was placed in deionized water and allowed to stand for 24 hours to dissolve the Sr3Al2O6 film to obtain the "PDMS / Ni 0.5 Zn 0.5 Fe2O4” heterogeneous structure; it should be understood that when the Sr3Al2O6 film is dissolved in deionized water, the Sr3Al2O6 film is attached to the SrTiO3 substrate, so the SrTiO3 substrate follows the Sr3Al2O6 film from the “PDMS / Ni 0.5 Zn 0.5 Fe2O4 / Sr3Al2O6 / SrTiO3" heterostructure; finally, the "PDMS / Ni 0.5 Zn 0.5 The "PDMS / NiFe2O4" heterostructure was removed from the deionized water and dried at 60 °C for 30 min. 0.5 Zn 0.5 Fe2O4” heterostructure.
[0072] Step 203: on a single crystal silicon (Si) substrate, a mixed solution for forming an organic film is spin-coated by a spin coating method to prepare an "organic film / Si" heterostructure. The specific process is as follows:
[0073] Step 203-1, dissolving PI powder in N,N-dimethylformamide DMF solvent to prepare a PI / DMF mixed solution for spin coating to form a PI film;
[0074] Step 203-2: spin-coat the PI / DMF mixed solution on a Si substrate and dry it to prepare a "PI / Si" heterostructure.
[0075] Specifically, a 5 μm thick PI organic film is spin-coated on a single crystal silicon (Si) substrate by spin coating. The preparation steps of the PI organic film include: dissolving 1 g of PI powder in 10 mL of N,N-dimethylformamide (DMF) solvent and magnetically stirring for 4 hours to obtain a mixed solution; spin coating the mixed solution on a Si substrate at a spin coating speed of 800 rpm; and then drying the Si substrate with the mixed solution at a drying temperature of 100°C for 6 hours to finally obtain a "PI / Si" heterostructure.
[0076] Step 204: 0.5 Zn 0.5Fe2O4 / PDMS" heterostructure and "organic film / Si" heterostructure were hot pressed to prepare an organic-based microwave absorbing composite material "organic film / Ni" filled with a two-dimensional ferrite film. 0.5 Zn 0.5 Fe2O4 / organic film", the specific process is as follows:
[0077] Step 204-1, "Ni 0.5 Zn 0.5 The "Fe2O4 / PDMS" heterostructure was hot pressed on the PI layer surface of the "PI / Si" heterostructure to prepare the "PDMS / Ni 0.5 Zn 0.5 Fe2O4 / PI / Si" heterostructure; among them, "Ni 0.5 Zn 0.5 Ni in Fe2O4 / PDMS” heterostructure 0.5 Zn 0.5 The Fe2O4 layer is in direct contact with the PI layer of the PI / Si heterostructure, and the hot pressing temperature is 250°C and the hot pressing time is 30 min;
[0078] Step 204-2: Use a physical method to peel off the PDMS layer (such as peeling with tweezers) to prepare "Ni 0.5 Zn 0.5 Fe2O4 / PI / Si” heterostructure;
[0079] Step 204-3, using another "PI / Si" heterostructure, physically peeling the PI layer from the Si substrate to obtain a PI film;
[0080] Step 204-4, hot pressing the above PI film on the "Ni 0.5 Zn 0.5 Ni in "Fe2O4 / PI / Si" heterostructure 0.5 Zn 0.5 The surface of the Fe2O4 layer was hot pressed at 250℃ for 30min to obtain "PI / Ni 0.5 Zn 0.5 Fe2O4 / PI / Si” heterostructure;
[0081] Step 204-5: Change "PI / Ni 0.5 Zn 0.5 The "Fe2O4 / PI / Si" was placed in a 250℃ vacuum drying oven, kept warm for 10 minutes, and then quickly placed in 0℃ deionized water. The "PI / Ni 0.5 Zn 0.5 Fe2O4 / PI / Si" can be peeled off from the Si substrate to obtain a multilayer composite material "PI / Ni0.5 Zn 0.5 Fe2O4 / PI”.
[0082] It should be noted that the PI film in the embodiment of the present invention can be directly replaced by a PEI film, and the process of preparing the "PEI / Si" heterostructure is similar to the process of preparing the "PI / Si" heterostructure. If the "PEI / Si" heterostructure is prepared in the experiment, the final product obtained in the experiment is "PEI / Ni 0.5 Zn 0.5 Fe2O4 / PEI".
[0083] The multilayer composite material PI / Ni obtained by the above preparation method 0.5 Zn 0.5 Fe2O4 / PI, firstly, organic polyimide (PI) as a high temperature resistant organic material has certain impedance matching characteristics; secondly, nickel zinc ferrite (Ni 0.5 Zn 0.5 Fe2O4) has strong initial magnetic permeability and saturation magnetization, and has excellent performance as a magnetic loss type absorbing material; then, due to the use of Ni 0.5 Zn 0.5 Large-sized two-dimensional ferrite of Fe2O4 material is filled into organic matter with impedance matching performance to form a layered composite material. The two-dimensional ferrite is a continuous film, which can prevent ferrite particles from agglomerating and completely suppress the passage of electromagnetic waves through the composite material, thereby achieving excellent absorbing effect and providing new ideas for the research and development of high-performance absorbing composite materials.
[0084] Embodiment 3
[0085] The present invention discloses a "PEI / Mn" filled with a two-dimensional ferrite film 0.5 Zn 0.5 A method for preparing a "Fe2O4 / PEI" organic-based wave-absorbing composite material, the method comprising the following steps:
[0086] Step 301: On a SrTiO3 single crystal substrate with a crystal orientation of (100), Mn 0.5 Zn 0.5 Fe2O4 target and Sr3Al2O6 target, and pulsed laser deposition technology was used to prepare the "Mn" filled with two-dimensional ferrite film 0.5 Zn 0.5 Fe2O4 / Sr3Al2O6 / SrTiO3" heterogeneous structure, the specific process is as follows:
[0087] Step 301-1, growing a Sr3Al2O6 thin film on a SrTiO3 single crystal substrate to prepare a "Sr3Al2O6 / SrTiO3" heterostructure;
[0088] Step 301-2: Growth of Mn in the “Sr3Al2O6 / SrTiO3” heterostructure 0.5 Zn 0.5 Fe2O4 thin film, prepared "Mn 0.5 Zn 0.5 Fe2O4 / Sr3Al2O6 / SrTiO3" heterostructure; among them, Mn 0.5 Zn 0.5 The Fe2O4 film is grown on the Sr3Al2O6 film side of the "Sr3Al2O6 / SrTiO3" heterostructure.
[0089] Specifically, a 50 nm thick Sr3Al2O6 film and a 50 nm thick Mn 0.5 Zn 0.5 When growing Sr3Al2O6 thin film, the temperature of SrTiO3 single crystal substrate is 800℃, the distance between Sr3Al2O6 target and SrTiO3 single crystal substrate is 6cm, and the laser energy is 2J / cm 2 , laser frequency is 3Hz, oxygen pressure is 15Pa, growth time is 10min, and the "Sr3Al2O6 / SrTiO3" heterostructure is prepared. 0.5 Zn 0.5 When Fe2O4 film is applied, the temperature of SrTiO3 single crystal substrate is 650℃, Mn 0.5 Zn 0.5 The distance between the Fe2O4 target and the SrTiO3 single crystal substrate is 6 cm, and the laser energy is 2 J / cm 2 , laser frequency is 3Hz, oxygen pressure is 5Pa, and growth time is 10min. Through the above process, "Mn 0.5 Zn 0.5 Fe2O4 / Sr3Al2O6 / SrTiO3” heterostructure.
[0090] Step 302: Using a water-soluble method, 0.5 Zn 0.5 Mn in the "Fe2O4 / Sr3Al2O6 / SrTiO3" heterostructure 0.5 Zn 0.5 Fe2O4 film peeling, and the preparation of "Mn 0.5 Zn 0.5 Fe2O4 / PDMS" heterostructure, the detailed process description is as follows:
[0091] Using the water dissolution method, Mn 0.5 Zn0.5 Fe2O4 thin film from "Mn 0.5 Zn 0.5 The specific process is as follows: First, a 50 μm thick polydimethylsiloxane (PDMS) film is attached to the “Mn 0.5 Zn 0.5 Fe2O4 / Sr3Al2O6 / SrTiO3" heterostructure; among them, PDMS film is adsorbed on "Mn 0.5 Zn 0.5 Mn in "Fe2O4 / Sr3Al2O6 / SrTiO3" heterostructure 0.5 Zn 0.5 Fe2O4 film side; then, the "PDMS / Mn 0.5 Zn 0.5 Fe2O4 / Sr3Al2O6 / SrTiO3" was placed in deionized water and allowed to stand for 24 hours to dissolve the Sr3Al2O6 film to obtain "PDMS / Mn 0.5 Zn 0.5 Fe2O4” heterogeneous structure; it should be understood that when the Sr3Al2O6 film is dissolved in deionized water, the Sr3Al2O6 film is attached to the SrTiO3 substrate, so the SrTiO3 substrate follows the Sr3Al2O6 film from the “PDMS / Mn 0.5 Zn 0.5 Fe2O4 / Sr3Al2O6 / SrTiO3" heterostructure; finally, the "Mn 0.5 Zn 0.5 The "Fe2O4 / PDMS" heterostructure was removed from the deionized water and dried at 60 °C for 30 min to obtain the "Mn 0.5 Zn 0.5 Fe2O4 / PDMS” heterostructure.
[0092] Step 303: On a single crystal silicon (Si) substrate, a mixed solution for forming an organic film is spin-coated by a spin coating method to prepare an "organic film / Si" heterostructure. The specific process is as follows:
[0093] Step 303-1, dissolving PEI powder in N-methylpyrrolidone (NMP) solvent to prepare a PEI / NMP mixed solution;
[0094] Step 303 - 2 , spin coating the PEI / NMP mixed solution on a Si substrate and drying the mixed solution to prepare a “PEI / Si” heterostructure.
[0095] Specifically, a 5 μm thick polyethyleneimine (PEI) organic film is spin-coated on a single crystal silicon Si substrate by spin coating. The preparation steps of the PEI organic film include: dissolving 1 g of PEI powder in 10 mL of NMP solvent and magnetically stirring for 4 hours to obtain a mixed solution; spin coating the mixed solution on a Si substrate at a spin coating speed of 800 rpm; and then drying the Si substrate with the mixed solution at a drying temperature of 125°C for 6 hours to finally obtain a "PEI / Si" heterostructure.
[0096] Step 304: 0.5 Zn 0.5 The organic-based microwave absorbing composite material "organic film / Mn" filled with two-dimensional ferrite film was prepared by hot pressing. 0.5 Zn 0.5 Fe2O4 / organic film", the specific process is as follows:
[0097] Step 304-1: Change “Mn 0.5 Zn 0.5 Fe2O4 / PDMS" heterostructure was hot pressed on the surface of "PEI / Si" heterostructure to prepare "PDMS / Mn 0.5 Zn 0.5 Fe2O4 / PEI / Si" heterostructure; among them, Mn 0.5 Zn 0.5 The Fe2O4 layer and the PEI layer were in direct contact, the hot pressing temperature was 230°C, and the hot pressing time was 30 min;
[0098] Step 304-2: Use a physical method to peel off the PDMS layer (such as peeling with tweezers) to prepare "Mn 0.5 Zn 0.5 Fe2O4 / PEI / Si” heterostructure;
[0099] Step 304-3, taking another "PEI / Si" heterostructure, and physically peeling the PEI layer from the Si substrate to obtain a PEI film;
[0100] Step 304-4, hot pressing the above PEI film on the "Mn 0.5 Zn 0.5 Mn in "Fe2O4 / PEI / Si" heterostructure 0.5 Zn 0.5 The surface of the Fe2O4 layer was hot pressed at 230℃ for 30min to obtain "PEI / Mn 0.5 Zn 0.5 Fe2O4 / PEI / Si” heterostructure;
[0101] Step 304-5: Add "PEI / Mn 0.5 Zn 0.5 The "Fe2O4 / PEI / Si" was placed in a 230℃ vacuum drying oven, kept warm for 10 minutes, and then quickly placed in 0℃ deionized water. The "PEI / Mn 0.5 Zn 0.5 Fe2O4 / PEI" can be peeled off from the Si substrate to obtain a multilayer composite material "PEI / Mn 0.5 Zn 0.5 Fe2O4 / PEI".
[0102] It should be noted that the PEI membrane in the embodiment of the present invention can be directly replaced by a PI membrane, and the process of preparing the "PI / Si" heterostructure is similar to the process of preparing the "PEI / Si" heterostructure. If the "PI / Si" heterostructure is prepared in the experiment, the final product obtained in the experiment is "PI / Mn 0.5 Zn 0.5 Fe2O4 / PI”.
[0103] The multilayer composite material PEI / Mn 0.5 Zn 0.5 Fe2O4 / PEI, firstly, polyethyleneimine (PEI) is also a high temperature resistant organic material with certain impedance matching characteristics; secondly, manganese zinc ferrite (Mn 0.5 Zn 0.5 Fe2O4) has strong initial magnetic permeability and saturation magnetization, and has excellent performance as a magnetic loss type absorbing material; then, due to the use of manganese zinc ferrite (Mn 0.5 Zn 0.5 Large-sized two-dimensional ferrite made of Fe2O4) material is filled into organic matter with impedance matching performance to form a layered composite material. The two-dimensional ferrite is a continuous film, which can avoid the agglomeration of ferrite particles and completely suppress the passage of electromagnetic waves through the composite material, thereby achieving excellent absorbing effect, providing new ideas for the research and development of high-performance absorbing composite materials.
[0104] Although the embodiments disclosed in the present invention are as above, the contents are only embodiments adopted to facilitate understanding of the present invention and are not intended to limit the present invention. Any technician in the field to which the present invention belongs can make any modifications and changes in the form and details of implementation without departing from the spirit and scope disclosed in the present invention, but the patent protection scope of the present invention shall still be subject to the scope defined in the attached claims.
Claims
1. A method for preparing an organic-based microwave absorbing composite material filled with a two-dimensional ferrite film, characterized in that: include: Step 1, on a single crystal substrate of SrTiO3, using a ferrite target and a Sr3Al2O6 target, a pulsed laser deposition technique is used to prepare a "ferrite / Sr3Al2O6 / SrTiO3" heterostructure; Step 2, using a water-soluble method to peel off the two-dimensional ferrite film in the "ferrite / Sr3Al2O6 / SrTiO3" heterostructure, and prepare a "ferrite / PDMS" heterostructure; Step 3, on a single crystal silicon substrate, a mixed solution for forming an organic film is spin-coated by a spin coating method to prepare an "organic film / Si" heterostructure; Step 4: hot-press the "ferrite / PDMS" heterostructure and the "organic film / Si" heterostructure by hot-pressing to prepare an organic / ferrite / organic multilayer absorbing composite material filled with a two-dimensional ferrite film.
2. The method for preparing an organic-based microwave absorbing composite material filled with a two-dimensional ferrite film according to claim 1, characterized in that: The step 1 comprises: using Ni 0.5 Zn 0.5 Fe2O4 target and Sr3Al2O6 target, and the "Ni" filled with two-dimensional ferrite film was prepared by pulsed laser deposition technology. 0.5 Zn 0.5 Fe2O4 / Sr3Al2O6 / SrTiO3” heterostructure; The step 2 comprises: using a water-soluble method to 0.5 Zn 0.5 Ni in the "Fe2O4 / Sr3Al2O6 / SrTiO3" heterostructure 0.5 Zn 0.5 The Fe2O4 film was peeled off and "Ni 0.5 Zn 0.5 Fe2O4 / PDMS” heterostructure; The step 3 comprises: on a single crystal silicon (Si) substrate, using a spin coating method to spin-coat a mixed solution for forming an organic film to prepare an "organic film / Si" heterostructure; The step 4 comprises: 0.5 Zn 0.5 The "Fe2O4 / PDMS" heterostructure and the "organic film / Si" heterostructure are hot pressed to prepare the organic-based microwave absorbing composite material "organic film / Ni" filled with a two-dimensional ferrite film. 0.5 Zn 0.5 Fe2O4 / organic film".
3. The method for preparing an organic-based microwave absorbing composite material filled with a two-dimensional ferrite film according to claim 2, characterized in that: The step 1 comprises: Step 1.1, growing a Sr3Al2O6 thin film on the SrTiO3 single crystal substrate to prepare a "Sr3Al2O6 / SrTiO3" heterostructure; Step 1.2, growing Ni on the "Sr3Al2O6 / SrTiO3" heterostructure 0.5 Zn 0.5 Fe2O4 film, prepared by 0.5 Zn 0.5 Fe2O4 / Sr3Al2O6 / SrTiO3" heterostructure; wherein the Ni 0.5 Zn 0.5 The Fe2O4 film is grown on one side of the Sr3Al2O6 film of the "Sr3Al2O6 / SrTiO3" heterostructure.
4. The method for preparing an organic-based microwave absorbing composite material filled with a two-dimensional ferrite film according to claim 2, characterized in that: The step 2 comprises: Step 2.1, in the "Ni 0.5 Zn 0.5 The "PDMS / Ni" heterostructure was prepared by electrostatically adsorbing polydimethylsiloxane PDMS film on the Fe2O4 / Sr3Al2O6 / SrTiO3" 0.5 Zn 0.5 Fe2O4 / Sr3Al2O6 / SrTiO3" heterogeneous structure; the PDMS film is adsorbed on the "Ni 0.5 Zn 0.5 "Fe2O4 / Sr3Al2O6 / SrTiO3" heterostructured Ni 0.5 Zn 0.5 Fe2O4 membrane side; Step 2.2, the "PDMS / Ni 0.5 Zn 0.5 The "Fe2O4 / Sr3Al2O6 / SrTiO3" heterostructure was placed in deionized water to dissolve the Sr3Al2O6 film and prepare the "Ni 0.5 Zn 0.5 Fe2O4 / PDMS” heterostructure.
5. The method for preparing an organic-based microwave absorbing composite material filled with a two-dimensional ferrite film according to claim 2, characterized in that: The step 3 comprises: Step 3.1, dissolving PI powder in N,N-dimethylformamide DMF solvent to prepare a PI / DMF mixed solution for spin coating to form a PI film; Step 3.2, spin coating the PI / DMF mixed solution on a Si substrate and drying it to prepare the "PI / Si" heterostructure.
6. The method for preparing an organic-based microwave absorbing composite material filled with a two-dimensional ferrite film according to claim 2, characterized in that: The step 4 comprises: Step 4.1, the "Ni 0.5 Zn 0.5 The "Fe2O4 / PDMS" heterostructure was hot pressed onto the PI layer surface of the PI / Si heterostructure prepared in step 1.3 to prepare the "PDMS / Ni 0.5 Zn 0.5 Fe2O4 / PI / Si" heterostructure; wherein the "Ni 0.5 Zn 0.5 The NiFe2O4 / PDMS" heterostructure 0.5 Zn 0.5 The Fe2O4 layer is in direct contact with the PI layer of the "PI / Si" heterostructure, the hot pressing temperature is 250°C, and the hot pressing time is 30 minutes; Step 4.2, using physical means to 0.5 Zn 0.5 The PDMS layer in the "Fe2O4 / PI / Si" heterostructure is peeled off to prepare "Ni 0.5 Zn 0.5 Fe2O4 / PI / Si” heterostructure; Step 4.3, using another PI / Si heterostructure, physically peeling the PI layer from the Si substrate to obtain a PI film; Step 4.4, hot pressing the PI film onto the "Ni 0.5 Zn 0.5 Ni in the "Fe2O4 / PI / Si" heterostructure 0.5 Zn 0.5 The surface of the Fe2O4 layer is prepared to obtain "PI / Ni 0.5 Zn 0.5 Fe2O4 / PI / Si” heterostructure; Step 4.5, the "PI / Ni 0.5 Zn 0.5 The "Fe2O4 / PI / Si" heterostructure was vacuum dried and kept warm, then placed in 0℃ deionized water, and the "PI / Ni 0.5 Zn 0.5 The Si layer in the "Fe2O4 / PI / Si" heterostructure is peeled off to prepare the organic-based microwave absorbing composite material PI / Ni filled with a two-dimensional ferrite film. 0.5 Zn 0.5 Fe2O4 / PI.
7. The method for preparing an organic-based microwave absorbing composite material filled with a two-dimensional ferrite film according to claim 2, characterized in that: The organic film is a polyimide PI film; or a polyethyleneimine PEI film.
8. The method for preparing an organic-based microwave absorbing composite material filled with a two-dimensional ferrite film according to claim 1, characterized in that: The step 1 comprises: using Mn 0.5 Zn 0.5 Fe2O4 target and Sr3Al2O6 target, and the "Mn" filled with two-dimensional ferrite film was prepared by pulsed laser deposition technology. 0.5 Zn 0.5 Fe2O4 / Sr3Al2O6 / SrTiO3” heterostructure; The step 2 comprises: using a water-soluble method to 0.5 Zn 0.5 Mn in the "Fe2O4 / Sr3Al2O6 / SrTiO3" heterostructure 0.5 Zn 0.5 The Fe2O4 film was peeled off and "Mn 0.5 Zn 0.5 Fe2O4 / PDMS” heterostructure; The step 3 comprises: on a single crystal silicon (Si) substrate, using a spin coating method to spin-coat a mixed solution for forming an organic film to prepare an "organic film / Si" heterostructure; The step 4 comprises: 0.5 Zn 0.5 The "Fe2O4 / PDMS" heterostructure and the "organic film / Si" heterostructure are hot pressed to prepare the organic-based microwave absorbing composite material "organic film / Mn" filled with a two-dimensional ferrite film. 0.5 Zn 0.5 Fe2O4 / organic film".
9. The method for preparing an organic-based microwave absorbing composite material filled with a two-dimensional ferrite film according to claim 8, characterized in that: The organic film is a polyethyleneimine PEI film; or a PI film.
10. An organic-based microwave absorbing composite material filled with a two-dimensional ferrite film, characterized in that: The organic-based absorbing composite material filled with a two-dimensional ferrite film is prepared by the preparation method described in any one of claims 1 to 7 or any one of claims 8 to 9, comprising: a ferrite film with a thickness of 50 to 200 nm and an organic film with a thickness of 3 to 7 μm; the organic-based absorbing composite material is a multilayer structure consisting of "organic film / ferrite film / organic film".
11. The organic-based microwave absorbing composite material filled with a two-dimensional ferrite film according to claim 10, characterized in that: The ferrite film includes one of the following films: Ni 0.5 Zn 0.5 Fe2O4 film, Mn 0.5 Zn 0.5 Fe2O4 film.
12. The organic-based microwave absorbing composite material filled with a two-dimensional ferrite film according to claim 10, characterized in that: The organic film includes one of the following thick films: a polyimide PI film and a polyethyleneimine PEI film.
13. The organic-based microwave absorbing composite material filled with a two-dimensional ferrite film according to claim 10, characterized in that: The multilayer structure of "organic film / ferrite film / organic film" includes: "PI / Ni 0.5 Zn 0.5 Fe2O4 / PI" multilayer structure, or, "PI / Mn 0.5 Zn 0.5 Fe2O4 / PI" multilayer structure, or, "PEI / Ni 0.5 Zn 0.5 Fe2O4 / PEI" multilayer structure, or, "PEI / Mn 0.5 Zn 0.5 Fe2O4 / PEI” multilayer structure.